Europol’s Counter-Terrorism Role: over 25 Years of Partnership - Antonio Ortiz (Belügyi Szemle)
Aim: Provide an overview of the evolution of Europol’s counter-terrorism capabilities over the last 25 years. Focus on the establishment of the European Counter Terrorism Centre (ECTC).